161. Assessing Antimicrobial Stewardship Engagement among Frontline Oncology Nurses and Chartering a Path Forward. (31st December 2020) - McCort, Margaret E; Bartash, Rachel; Cowman, Kelsie; Sakalian, Susan; Sheridan, Carol; Wright, Karen; Hopkins, Una T; Nori, Priya; Nori, Priya
Abstract: Background: Developing robust, multidisciplinary antimicrobial stewardship programs to combat drug resistance is a priority of healthcare institutions, in accordance with Joint Commission standards and national legislature. However, the involvement of nurses in stewardship programs has trailed behind that of physicians and pharmacists, despite their unique position as frontline providers. In particular, oncology nursing staff can play a key role in extending stewardship to their high acuity patients, who frequently require antimicrobials. We sought to conduct a survey study of oncology nursing providers on their understanding, perceptions, and attitudes about antimicrobial stewardship. Methods: A voluntary and anonymous survey was emailed to oncology nursing staff on adult and pediatric oncology wards and clinics throughout our hospital system. We used an adapted 28-item Likert scale-based survey to assess understanding of antimicrobial stewardship attitudes and perceived barriers to greater involvement in stewardship programs. A survey reminder was emailed weekly for 8 weeks and completion was encouraged by nursing leadership in unit staff meetings. Results: The survey was emailed to 281 nurses, of whom 39% (n=109) responded. 54.1% of nurses believed that an antibiotic stewardship program was very important in their healthcare setting. However, 56% of respondents were unfamiliar with the meaning of antibiotic stewardship, and 83.5% were not aware of how to contact the antimicrobial stewardship team with questions. More than 75% felt that nurses could help with antibiotic use, though 76% indicated wanting to know more about which antibiotics treat different infections and 74% wanted to know more about appropriate durations of antibiotics. Conclusion: Oncology nurses have the potential to play a valuable role in antimicrobial stewardship. Barriers to nursing involvement include knowledge gaps on antibiotics and unfamiliarity with existing stewardship programs and their functions within hospital systems. Nursing education and orientation to available resources are key steps to involving nursing staff in antimicrobial stewardship programs, maximizing benefits for both patients and hospitals. Disclosures: All Authors : No reported disclosures